2009
DOI: 10.1073/pnas.0912082106
|View full text |Cite
|
Sign up to set email alerts
|

Activity-independent specification of synaptic targets in the posterior lateral line of the larval zebrafish

Abstract: The development of functional neural circuits requires that connections between neurons be established in a precise manner. The mechanisms by which complex nervous systems perform this daunting task remain largely unknown. In the posterior lateral line of larval zebrafish, each afferent neuron forms synaptic contacts with hair cells of a common hair-bundle polarity. We investigated whether afferent neurons distinguish hair-cell polarities by analyzing differences in the synaptic signaling between oppositely po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Finally, the extension of projections toward nearby afferent terminals reduces a terminal's search for new synaptic sites from three dimensions to only one. Because polarity-specific innervation of lateral line hair cells occurs in the absence of hair cell activity, a chemoaffinity mechanism may be responsible for partner matching (Nagiel et al 2009). Although hair cell projections are more likely to extend into the vicinity of mature hair cells of the same polarity, this predilection alone is unlikely to confer specific innervation inasmuch as afferent terminals of both functional polarities reside beneath mature hair cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the extension of projections toward nearby afferent terminals reduces a terminal's search for new synaptic sites from three dimensions to only one. Because polarity-specific innervation of lateral line hair cells occurs in the absence of hair cell activity, a chemoaffinity mechanism may be responsible for partner matching (Nagiel et al 2009). Although hair cell projections are more likely to extend into the vicinity of mature hair cells of the same polarity, this predilection alone is unlikely to confer specific innervation inasmuch as afferent terminals of both functional polarities reside beneath mature hair cells.…”
Section: Discussionmentioning
confidence: 99%
“…From the posterior lateral line ganglion, which lies immediately caudal to the ear, several bipolar neurons extend sensory axons to contact a neuromast (Metcalfe et al 1985). Each afferent fiber receives synaptic input from hair cells of only one polarity, a specificity that occurs independently of hair cell activity (Nagiel et al 2008(Nagiel et al , 2009). To learn how this synaptic pattern arises, we studied synapse formation by newly differentiated hair cells in larvae 2-4 d post-fertilization (dpf).…”
mentioning
confidence: 99%
“…A recent study examined afferent innervation of lateral line neuromasts in zebrafish mutants lacking vesicular glutamate transporter 3 (Vglut3), the transporter responsible for filling hair cell synaptic vesicles with glutamate (Nagiel et al, 2009;Obholzer et al, 2008). They reported no significant difference in the mean fraction of hair cells innervated by a single afferent neuron in vglut3 mutants verses wild type, and concluded that synaptic transmission did not appear to be essential for synaptic maintenance (Nagiel et al, 2009). These results suggest that Ribeye is probably playing a crucial structural role, perhaps by recruiting additional molecules to stabilize synaptic connections.…”
Section: Discussionmentioning
confidence: 99%
“…The agarose covering the right side of the larva was scraped away with a 31.5-gauge syringe needle so that the right inner ear was exposed for positioning the stimulus probe and recording electrode. The top of the larva was then covered with a 0.25-ml solution containing 116 mM NaCl, 2.9 mM KCl, 1.8 mM CaCl 2 , and 5.0 mM Hepes (pH=7.2;Nagiel et al 2009) to prevent the agarose from drying. The recording chamber was placed in a Petri dish holder that was temperature controlled at ∼28.5°C (Model TC-344B, Warner Instruments, Hamden, CT).…”
Section: Zebrafish Care and Mountingmentioning
confidence: 99%